Feeding Practices and Associated Factors During Diarrheal Disease Among Children Aged Less Than Five Years: Evidence from the Ethiopian Demographic and Health Survey 2016 - Tsehay CT; Aschalew AY; Dellie E; Gebremedhin T (Dove Medical Press, 2021)
Chalie Tadie Tsehay, Andualem Yalew Aschalew, Endalkachew Dellie, Tsegaye Gebremedhin Department of Health Systems and Policy, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Andualem Yalew AschalewUniversity of Gondar, P. O. Box: 196, Gondar, EthiopiaTel +251918151825Email yalewandualem@gmail.comPurpose: Diarrhea is a common childhood illness and one of the leading causes of death in young children globally. In Ethiopia, a significant number of deaths and hospitalizations in under-five children are related to diarrheal diseases. Inappropriate feeding during diarrhea leads to a double burden of diarrhea recurrence and malnutrition among children. However, empirical evidence is limited in Ethiopia. Thus, this study was aimed to assess feeding practices and associated factors during diarrheal disease among children aged less than five years in Ethiopia.Patients and Methods: The study used the Ethiopian Demographic and Health Survey (EDHS) 2016 data. A two-stage stratified sampling technique was applied to identify 917 under five years children. Generalized linear mixed model analyses were computed, and a P value of less than 0.05 and an adjusted odds ratio (AOR) with a 95% confidence interval (CI) were used to identify statistically significant factors with feeding practices.Results: The majority (92.5%) of mothers were married. Out of the participants, (54.1%) of children were male; 55.6% of them were in the age group of 6– 23 months. The appropriate feeding practices for children aged less than five years who had diarrhea was 15.4% (95% CI: 13.7%-18.2%). Mothers aged 25– 34 years (AOR: 0.6, 95% CI: 0.4– 0.9), agricultural occupation of mothers (AOR: 2.2, 95% CI: 1.3– 3.6), mothers attended four and more antenatal visit (AOR: 2.3, 95% CI: 1.3– 4.32) and mothers who had a postnatal checkup within two months of birth (AOR: 1.9, 95% CI: 1.1– 3.2) were factors statistically associated with child feeding practices during diarrhea.Conclusion: Less than one-fifth of under-five children practiced appropriate feeding during diarrheal disease. Working in agriculture and attending antenatal care and postnatal checkup within two months were positively influencing feeding practice. Therefore, the government of Ethiopia needs to strengthen the existing maternal and child health services.Keywords: feeding practices, diarrheal disease, under-five children, Ethiopia